Gecko phylogeography in the Western Indian Ocean region: the oldest clade of Ebenavia inunguis lives on the youngest island. (2nd December 2016) - Hawlitschek, Oliver; Toussaint, Emmanuel F. A.; Gehring, Philip‐Sebastian; Ratsoavina, Fanomezana M.; Cole, Nik; Crottini, Angelica; Nopper, Joachim; Lam, Athena W.; Vences, Miguel; Glaw, Frank
Abstract: Aim: We studied the gecko genus Ebenavia to reconstruct its colonization history, test for anthropogenic versus natural dispersal out of Madagascar, and correlate divergence date estimates of our phylogeny with geological age estimates of islands in the region. Location: Madagascar and surrounding islands of the Western Indian Ocean (Comoros, Mayotte, Mauritius, Pemba). Methods: We reconstructed the phylogeny of Ebenavia covering its entire geographical range using a molecular data set of three mitochondrial and two nuclear markers. We estimated divergence times based on calibrations using (1) previously calculated mutation rates of mitochondrial markers, (2) a combination of these rates with old or (3) young geological age estimates for some of the islands inhabited by the genus, and (4) an independent data set with fossil outgroup calibration points. Results: Ebenavia inunguis, one of two recognized species of the genus, comprises multiple ancient evolutionary lineages. The earliest divergence within this complex (Miocene, 13–20 Ma; 95% credibility interval [CI]: 4–29 Ma) separates the population of the Comoros Islands, excluding Mayotte, from all other lineages. The age estimates for island lineages coincide with the geological age estimates of the islands except for Grand Comoro, where the age of the local clade (3–5 Ma; 95% CI: 2–7 Ma) significantly predates the estimated island age (0·5 Ma). A clade from north Madagascar + Mayotte + Pemba is estimated to have diverged from an eastern Malagasy clade in the Miocene. Main Conclusions: Our results suggest that Grand Comoro Island is geologically older than previously estimated. The islands of the Comoros and Pemba were probably colonized via natural dispersal out of Madagascar (> 1000 km in the case of Pemba). Mauritius was most likely colonized only recently from eastern Madagascar via human translocation.